Vehicle routing with cross-dock selection. (January 2017) - Maknoon, Yousef; Laporte, Gilbert
Abstract: The vehicle routing problem with cross-dock selection is a variant of the vehicle routing problem containing spatial and load synchronization constraints by which products are transferred and processed via at least one cross-dock. This paper presents a mathematical formulation of the problem and an adaptive large neighborhood search heuristic. Computational experiments on a set of benchmark instances demonstrate the efficiency of the proposed methodology. Abstract : Highlights: We consider a pickup and delivery problem with cross-docks. All requests transit through at least one cross-dock. We formulate the problem as a mixed integer linear program. We develop an adaptive large neighborhood search heuristic for it. This heuristic consistently yields optimal or near-optimal solutions.